Meningkatkan Kepedulian Terhadap Lingkunggan dan Menjaga Kebersihan Sekolah di Yayasan Al-Amin Gersik Kediri Lombok Barat - Azhari, Supian; Azizah Nurul Fadlilah; Hadlun; Andrian Firdaus; M. Tabrani; Nuraini; Sofian Prawiya Hadi; Irfan Hidayat; Ahyar Rosyidi; Ilhami Kurniati; Pebriyati Ria Rahayu; Azizah Fitriana; Latifatul Rahma; Fitri Handayani; Novi Sutrisna (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Character is something that exists in each individual who is formed in the family environment since childhood. However, character also exists in each individual from birth. Good character can be formed through education, one of which is through character education in schools. To make it happen, it can be done by instilling character values in students. One of the characters that must be formed from an early age is the character that cares for the environment. The formation of a caring character for the environment can be started from the school environment by keeping the school clean. By getting used to students protecting the school environment, students will care about the environment around them. Programs that are usually carried out in schools have elements of K3 (cleanliness, beauty, neatness), including pickets together in classrooms and in the school environment as well as learning to care for plants and take care of them. This program aims to strengthen and increase awareness activities of students in schools in order to keep the environment clean and take care of the surrounding plants. Because with a clean school environment, it will make students and teachers comfortable in carrying out teaching and learning activities.